Classifications, Advantages, Disadvantages, Toxicity Effects of Natural and Synthetic Dyes: A review - Sajda .S. Affat, (University of Thi-Qar Journal of Science, 2021)
Dyes are complex organic compounds, which are used by various industries to colour their products. Natural and synthetic dyes are compounds of great interest since they play an important role in our everyday life. The broad variety of technical and industrial applications, which is used for dyeing or printing of textile, paper, leather and other materials. Some of these dyes are toxic, carcinogenic and can cause skin and eye irritation. Many carcinogenic and allergic synthetic dyes are banned now. Many dyes, though not banned yet, may not be completely safe. Most synthetic dyes are not biodegradable; they accumulate on lands and in river causing ecological problems. Dyes from natural resources such as vegetables, animals and minerals were popular before the invention of synthetic dyes. The efforts have been made to substitute harmful synthetic dyes with natural counterpart. However, natural dyes should be selected with caution – some are neither eco-friendly nor good performer. This review paper provides extensive literature information about dyes, its classification, advantages, disadvantages and toxicity effects.